Words of Warfare: Life of Mission Soldiers in the Perspective of Quantitative Linguistics - Radková, Lucie; Místecký, Michal (Bohemistyka, 2021)
The paper focuses on the analysis of a sample of military language from the stylometric perspective. The corpus is the chronicle of the 8th Czech Armed Forces Guard Company, which operated at the Bagram Air Field base (BAF). We work on the assumptions that in the corpus, there will be (A) a prominent presence of military slang; (B) a high proportion of abbreviations; (C) frequent linguistic devices expressing mutuality and collectiveness of the soldiers’ enterprise. The texts were subjected to keyword and collocation analyses; these determined several stylistic features of theirs (such as use of English-based expressions, protocol-like language, or idiosyncratic collocations), which testify to the multifaceted character of the military chronicle genre.